Maternal Hypertensive Pregnancy Disorders and Mental Disorders in Children. Issue 6 (June 2020) - Lahti-Pulkkinen, Marius; Girchenko, Polina; Tuovinen, Soile; Sammallahti, Sara; Reynolds, Rebecca M.; Lahti, Jari; Heinonen, Kati; Lipsanen, Jari; Hämäläinen, Esa; Villa, Pia M.; Kajantie, Eero; Laivuori, Hannele; et al.
Abstract : The associations of maternal hypertensive pregnancy disorders with offspring mental disorders remain unclear. We examined whether maternal hypertensive disorders and maximum blood pressure during pregnancy predict offspring childhood mental disorders, whether the associations are independent of maternal and paternal mental disorders and paternal hypertensive disorders, independent of or additive with maternal early pregnancy overweight/obesity and diabetes mellitus disorders, and mediated or moderated by preterm birth, small-for-gestational-age birth and neonatal intensive care unit admission. Our prospective study comprised 4743 mother-child dyads of Prediction and Prevention of Preeclampsia and Intrauterine Growth Restriction study. Women were recruited to the study in early pregnancy at Finnish maternity hospitals. Children were born 2006 to 2010 and followed-up until December 31, 2016, to ages 6.4 to 10.8 years. Hypertensive pregnancy disorders were identified from medical records, Medical Birth Register, and Care Register for Health Care. Systolic and diastolic blood pressure were measured at antenatal clinics and hospital visits. Mental disorder diagnoses were identified from Care Register for Health Care. Maternal gestational and chronic hypertension, preeclampsia and its severity increased offspring hazard of any childhood mental disorder. The associations of preeclampsia (hazard ratio=1.66 [95% CI, 1.14–2.42]) and severe preeclampsia (hazard ratio=2.01 [95% CI, 1.08–3.73]) were independent of all covariates. Maternal hypertensive and diabetes mellitus disorders and overweight/obesity also additively increased offspring hazard of mental disorders. Preterm and small-for-gestational-age births and neonatal intensive care unit admission partially mediated the effects of any and severe preeclampsia on offspring mental disorders. To conclude, maternal hypertensive pregnancy disorders carry adverse consequences for offspring mental health. Abstract : Supplemental Digital Content is available in the text.